Fresh flavours from dried food - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The need to preserve food in times of plenty against the times of shortage has been faced from time immemorial. Probably the oldest and most usual method is air-drying which is simple fast and cheap. The only problem is that the appearance, texture...